Analisis Implementasi Sistem Akuntansi Dan Pengelolaan Keuangan Pada Bank Sampah Kelurahan Bener Kota Yogyakarta - Fahrul Imam Santoso; Widiyanti Kurnianingsih (Jurnal Akuntansi dan Pajak, 2020)
In order to realize public awareness of the environment, through PP No.13 of 2012 regarding the need for a paradigm shift in waste management, the government through the village level government promoted the garbage bank program as a form of government concern with the community to protect the environment in applying the 3R principle (Reduce, Reuse, and Recycle). The purpose of this study was to analyze the application of the accounting and financial management system to a garbage bank in the Bener Village, Yogyakarta City. This research is a comparative descriptive qualitative research that describes the implementation of the accounting system and financial management of waste banks in the Bener Village then compares it with the accounting cycle starting from recording transactions to preparing financial statements and how to manage their finances, so a conclusion can be drawn. Analysis tools in data processing in this study using the Nvivo11 program. The results of this study indicate that the implementation of the accounting system and financial management of waste banks in the Bener Village has not been carried out thoroughly and consistently according to the rules of the proper accounting cycle so that it needs to be restructured so that the accounting process at the Waste Bank in the Bener Village can run well.